Teaching of the written alphabet. A theoretical reflection about graphic advertising (Quaestiones Disputatae: temas en debate, 2017)
This article presents a theoretical reflection on the possible improvement of the initial process of the written alphabet by means of the influence of graphic advertising. It sets out a methodological and didactical strategy using the “Sharea Coca-Cola” commercial as a basis. It’s purpose is to support the initial writtenformative processes and the development of the theme in the classroom, especiallyin the first grade of primary. It gives an empistemological insight from a teaching and social communication perspective, supported by the concepts of advertising, graphic adversting, writing and the initiation of the written alphabet. Besides this, some activities are suggested that arise from the commercial along with some considerations that must be taken in to account upon starting the process of the written alphabet.
Keywords: advertising; graphic advertising; infancy; writing; written alphabet; writing teaching